2016
DOI: 10.1177/1053815116636645
|View full text |Cite
|
Sign up to set email alerts
|

Peer Modeling of Commenting During Small Group Direct Instruction for Academic Behaviors

Abstract: During small group instruction, two groups of children-each group comprised of one child with a disability and two without disabilities-were taught to read words using a progressive time delay procedure (PTD). Apart from the children with disabilities, two typically developing peers in each group were taught to comment on tokens given for correct responding. Academic responding was similar to that in previous studies including older children, but observational learning of peers' words was variable within and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Additionally, Twitter seems to be an effective tool to facilitate peer learning, providing dual affordances. A number of studies, in settings from elementary school through higher education, have found peer modeling to facilitate student learning (Ledford & Wolery, 2013;Murphy, 2015;Richards, Heathfield, & Jenson, 2010;Urlacher, Wolery, & Ledford, 2016). In the present study, Twitter was found to facilitate peer modeling, in which students were able to learn from peer tweets, helping them to better understand assignments or to compare their own work as a measure of adequacy.…”
Section: Theme 1: Transformation Of Teaching and Learningsupporting
confidence: 47%
“…Additionally, Twitter seems to be an effective tool to facilitate peer learning, providing dual affordances. A number of studies, in settings from elementary school through higher education, have found peer modeling to facilitate student learning (Ledford & Wolery, 2013;Murphy, 2015;Richards, Heathfield, & Jenson, 2010;Urlacher, Wolery, & Ledford, 2016). In the present study, Twitter was found to facilitate peer modeling, in which students were able to learn from peer tweets, helping them to better understand assignments or to compare their own work as a measure of adequacy.…”
Section: Theme 1: Transformation Of Teaching and Learningsupporting
confidence: 47%
“…Small group instruction prepares children for elementary school and later grades, specifically by teaching children how to learn. Urlacher, Wolery, and Ledford (2016) found that preschoolers with and without special needs could learn to name sight words and practice social skills (make a comment to a peer) during the same brief sessions (10 min each). Children participated in these sessions in the classrooms while sitting at a table, on the floor, or on the playground.…”
mentioning
confidence: 94%
“…Even when recommended and evidence-based practices are used (e.g., Division for Early Childhood, 2014), practitioners must make numerous decisions regarding how they are used (cf. Ledford et al, 2016). Trial arrangement is one such decision.…”
mentioning
confidence: 99%
“…Progressive time delay (PTD) has been used in both massed (e.g., Urlacher, Wolery, & Ledford, 2016) and embedded (e.g., Venn et al, 1993) trial arrangements in early childhood settings. During initial sessions, children are immediately prompted to engage in desired behavior, reducing the opportunity for errors (Wolery, Ault, & Doyle, 1992).…”
mentioning
confidence: 99%